KEWAJIBAN PERUBAHAN BENTUK HUKUM BUMD DARI PERUSAHAAN DAERAH MENJADI PERUSAHAAN UMUM DAERAH (STUDI DI PDAM TIRTA GALAHERANG KABUPATEN MEMPAWAH) - Atma, Dzaki Dwi; Patra, Rommy (Faculty of Law, Universitas Tanjungpura, 2023)
Abstract PDAM Tirta Galaherang is currently still a regional company that has not yet turned into a regional public company because there is no approval of the regional regulation draft that has been prepared by the local government and PDAM Tirta Galaherang. Since the promulgation of Law Number 23 of 2014 concerning Regional Government, Regional Owned Enterprises (BUMD) only have a clear definition, namely based on Article 402 paragraph (2) of the 2014 Law concerning Regional Government which reads